Mapping travel : the origins and conventions of western journey maps - Dym, Jordana, 1967- (Brill, 2021)
Drawing on a thousand years of European travel writing and mapmaking, Dym suggests that after centuries of text-based itineraries and on-the spot directions guiding travelers and constituting their reports, maps in the fifteenth century emerged as tools for Europeans to support and report the results of land and sea travel. With each succeeding generation, these linear journey maps have become increasingly common and complex, responding to changes in forms of transportation, such as air and motor car 'flight' and print technology, especially the advent of multi-color printing. This is their story.
Keywords: Cartography -- Europe -- History.; Early maps -- Europe -- History.; Europe -- Description and travel.; Cartographie -- Europe -- Histoire.; Cartes anciennes -- Europe -- Histoire.; Europe -- Descriptions et voyages.; Cartography; Early maps; Travel; Europe; History